Antioxidative and Antimicrobial Evaluation of Bark Extracts from Common European Trees in Light of Dermal Applications - Sissy Häsler Gunnarsdottir; Lukas Sommerauer; Thomas Schnabel; Gertie Janneke Oostingh; Anja Schuster (MDPI AG, 2023)
Plant species have developed effective defense strategies for colonizing diverse habitats and protecting themselves from numerous attacks from a wide range of organisms, including insects, vertebrates, fungi, and bacteria. The bark of trees in particular constitutes a number of components that protect against unwanted intruders. This review focuses on the antioxidative, dermal immunomodulatory, and antimicrobial properties of bark extracts from European common temperate trees in light of various skin pathogens, wound healing, and the maintenance of skin health. The sustainability aspect, achieved by utilizing the bark, which is considered a byproduct in the forest industry, is addressed, as are various extraction methods applied to retrieve extracts from bark.